Psychographic Constructs and Consumer Purchase Intention in Kenyan Context - Wambui Kiboro, Grace; Iravo, Mike; Mbugua, Doris; Owino, Edward (British Journal of Marketing Studies, 2020)
Competitiveness in the retail sector calls for an understanding of psychographic constructs and their potent drive of consumer purchase intention. The study examined psychographic constructs in terms of the effect of personality on consumer purchase intention in supermarkets and the effect of lifestyle on consumer purchase intention in supermarkets in Nairobi, Kenya. The study was grounded on Freud’s theory of personality and social learning theory of consumer behaviour. Anchoring on a positivist philosophy, a descriptive cross-sectional survey was employed in studying 48 supermarkets. Using quota sampling, a final sample of 384 consumers was drawn from 48 anchor supermarkets under study. Data from the validated questionnaire was subjected to descriptive statistical analysis and multivariate regression analysis. Both personality and lifestyle had a positive and significant effect on consumer purchase intention and therefore the effect of psychographic constructs on consumer purchase intention was significant and positive. The larger effect size of lifestyle meant supermarket managers should pay more attention to attributes of consumer lifestyle